2005
DOI: 10.1097/00008469-200506000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of myeloperoxidase and catechol-O-methyltransferase and breast cancer risk

et al.

Abstract: This nested case-control study evaluated the role of polymorphisms in the myeloperoxidase (MPO) and catechol-O-methyltransferase (COMT) genes that modulate oxidative stress in breast cancer risk in a Chinese population. Our results demonstrate that the MPO A/A genotype was associated with a reduced risk of breast cancer (odds ratio (OR) 0.64; 95% confidence interval (CI) 0.11-3.76), whereas there was no overall association of COMT genotype with breast cancer. Of note, an elevated breast cancer risk associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
3
16
1
Order By: Relevance
“…We found a non-significant inverse association between MPO homozygous variant genotype and breast cancer risk, providing weak support for this biologically plausible hypothesis. This result was consistent with two previous studies, which both reported a decreased breast cancer risk associated with MPO AA genotype [17,18]. In the Long Island Breast Cancer Project, Ahn et al observed a non-significant 17% reduction in risk associated with being homozygous for the A allele [17].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found a non-significant inverse association between MPO homozygous variant genotype and breast cancer risk, providing weak support for this biologically plausible hypothesis. This result was consistent with two previous studies, which both reported a decreased breast cancer risk associated with MPO AA genotype [17,18]. In the Long Island Breast Cancer Project, Ahn et al observed a non-significant 17% reduction in risk associated with being homozygous for the A allele [17].…”
Section: Discussionsupporting
confidence: 91%
“…In the Long Island Breast Cancer Project, Ahn et al observed a non-significant 17% reduction in risk associated with being homozygous for the A allele [17]. Lin et al found that women with the MPO AA genotype had an OR of 0.64 (95% CI, 0.11-3.76) in a Chinese population [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these negative results do not entirely exclude the potential role of polymorphisms of these genes in the aetiology of breast cancer, even though similar results were reported by previous studies. 22,23 In addition, although the results from our study indicated that SNPs of MnSOD1183T.C and GPx1Pro198Leu showed significant association with the risk of breast cancer, O 2…”
Section: á2mentioning
confidence: 57%